Arsenic abrogates the estrogen-signaling pathway in the rat uterus - Chatterji Urmi; Chatterjee Aniruddha (BMC, 2010)
Abstract Background Arsenic, a major pollutant of water as well as soil, is a known endocrine disruptor, and shows adverse effects on the female reproductive physiology. However, the exact molecular events leading to reproductive dysfunctions as a result of arsenic exposure are yet to be ascertained. This report evaluates the effect and mode of action of chronic oral arsenic exposure on the uterine physiology of mature female albino rats. Methods The effect of chronic oral exposure to arsenic at the dose of 4 microg/ml for 28 days was evaluated on adult female albino rats. Hematoxylin-eosin double staining method evaluated the changes in the histological architecture of the uterus. Circulating levels of gonadotropins and estradiol were assayed by enzyme-linked immunosorbent assay. Expression of the estrogen receptor and estrogen-induced genes was studied at the mRNA level by RT-PCR and at the protein level by immunohistochemistry and western blot analysis. Results Sodium arsenite treatment decreased circulating levels of estradiol in a dose and time-dependent manner, along with decrease in the levels of both LH and FSH. Histological evaluation revealed degeneration of luminal epithelial cells and endometrial glands in response to arsenic treatment, along with reduction in thickness of the longitudinal muscle layer. Concomitantly, downregulation of estrogen receptor (ER alpha), the estrogen-responsive gene - vascular endothelial growth factor (VEGF), and G1 cell cycle proteins, cyclin D1 and CDK4, was also observed. Conclusion Together, the results indicate that arsenic disrupted the circulating levels of gonadotropins and estradiol, led to degeneration of luminal epithelial, stromal and myometrial cells of the rat uterus and downregulated the downstream components of the estrogen signaling pathway. Since development and functional maintenance of the uterus is under the influence of estradiol, arsenic-induced structural degeneration may be attributed to the reduction in circulating estradiol levels. Downregulation of the estrogen receptor and estrogen-responsive genes in response to arsenic indicates a mechanism of suppression of female reproductive functions by an environmental toxicant that is contra-mechanistic to that of estrogen.